Tissue-Specific Transcriptome and Hormonal Regulation of Pollinated and Parthenocarpic Fig (Ficus carica L.) Fruit Suggest that Fruit Ripening Is Coordinated by the Reproductive Part of the Syconium - Rosianski, Yogev; Doron-Faigenboim, Adi; Freiman, Zohar E.; Lama, Kumar; Milo-Cochavi, Shira; Dahan, Yardena; Kerem, Zohar; Flaishman, Moshe A. (Frontiers in Plant Science, 2016)
In the unconventional climacteric fig (Ficus carica) fruit, pollinated and parthenocarpic fruit of the same genotype exhibit different ripening characteristics. Integrative comparative analyses of tissue-specific transcript and of hormone levels during fruit repining from pollinated vs. parthenocarpic fig fruit were employed to unravel the similarities and differences in their regulatory processes during fruit repining. Assembling tissue-specific transcripts into 147,000 transcripts with 53,000 annotated genes provided new insights into the spatial distribution of many classes of regulatory and structural genes, including those related to color, taste and aroma, storage, protein degradation, seeds and embryos, chlorophyll, and hormones. Comparison of the pollinated and parthenocarpic tissues during fruit ripening showed differential gene expression, especially in the fruit inflorescence. The distinct physiological green phase II and ripening phase III differed significantly in their gene-transcript patterns in both pulp and inflorescence tissues. Gas chromatographic analysis of whole fruits enabled the first determination of ripening-related hormone levels from pollinated and non-pollinated figs. Ethylene and auxin both increased during fruit ripening, irrespective of pollination, whereas no production of active gibberellins or cytokinins was found in parthenocarpic or pollinated ripening fruit. Tissue-specific transcriptome revealed apparent different metabolic gene patterns for ethylene, auxin and ABA in pollinated vs. parthenocarpic fruit, mostly in the fruit inflorescence. Our results demonstrate that the production of abscisic acid (ABA), non-active ABA–GE conjugate and non-active indoleacetic acid (IAA)–Asp conjugate in pollinated fruits is much higher than in parthenocarpic fruits. We suggest that fruit ripening is coordinated by the reproductive part of the syconium and the differences in ABA production between pollinated and parthenocarpic fig fruit might be the key to their different ripening characteristics.